An innovative LFC scheme for multi-area microgrid incorporating with hydrogen-based demand response mechanism - Yildiz, Suleyman; Gunduz, Hasan; Yildirim, Burak; Ozdemir, Mahmut Temel (Pergamon-Elsevier Science Ltd, 2023)
Due to the unpredictability of renewable energy sources (RESs) in Microgrids (MG), the Load Frequency Control (LFC) mechanism is crucial for frequency management of these systems. Frequency control in MGs can be made more cost-effective with the help of demandside management by temporarily boosting or decreasing power usage, in addition to Automatic Generation Control (AGC) techniques. Hydrogen can provide considerable benefits to MGs since it can be used in two ways: as a fuel cell for electricity generation or as an electrolyzer for power consumption, satisfying the needs of AGC and demand response (DR) simultaneously utilizing Hydrogen Energy Storage (HES) system. This research proposes an MG structure that integrates appropriate energy storage technologies, is able to provide both energy and waste management, and enables use of a variety of RES (including solar, wind, wastewater, agricultural, and residential wastes). With the newly announced Improved-Salp Swarm Algorithm (ISSA), this research aims to design a novel double-input interval type-2 fuzzy fractional order proportional-integral-derivative PI + TID (DIT2-FOPI + TID) cascade controller for LFC of multi-area MGs considering DR with a broad range of Distributed energy resources (DER). In all case studies, the proposed controller demonstrates outstanding effectiveness within the setting of LFC of MGs and, especially by employing DRM approaches, boosts frequency response performance by up to 65%. The results indicate that the dynamic frequency response of the MG is significantly enhanced by the addition of DRM capability with the HES system. (c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Type-2 fuzzy logic controller; Demand response; Hydrogen fuel cell; Improved salp swarm algorithm; LFC